Kontribusi Kekuatan Otot Tungkai Dengan Kemampuan Tendangan Shooting Dalam Permainan Sepak Bola Siswa SMA N 1 Tirawuta Kabupaten Kolaka Timur - Halmadrin, Resky Ana Abadi, Basman (Jurnal Ilmu Sosial Dan Pendidikan, 2024)
The aim of this research is to determine the contribution of leg muscle strength to shooting kick ability in the soccer game of students at SMA N 1 Tirawuta, East Kolaka Regency. The data analysis technique used is descriptive statistical analysis using the SPSS program by calculating the average value, standard deviation, mode, median, maximum value and minimum value. Before testing, the hypothesis test is first carried out by the equality test, namely the normality test and the linearity test. . Based on data analysis, the Sig value is obtained. (2-tailed) is 0.033 smaller than 0.05, the correlation of 0.668 is in the high correlation category. The coefficient of determination is 0.390, meaning that leg muscle strength has a contribution to shooting ability in soccer games and has a moderate correlation.